Advances in biological and medical physics. - Lawrence, John H. (John Hundale), 1904-1991; Tobias, Cornelius A. (Academic Press Inc., 1958)
Advances in Biological and Medical Physics, Volume VI, provides an overview of the state of knowledge in biological and medical physics. The book opens with a study on ion and water transport in stomach and intestine. This is followed by separate chapters on artificial and induced periodicity in living cells; radiobiological aspects of the induction of lysogenic bacteria to produce phage with x-ray, gamma ray, and ultraviolet radiations; cell studies with microspectrography; and the effect of ionizing radiation on tumors in experimental animals. Subsequent chapters deal with biological effects.